2007
DOI: 10.1099/mic.0.2006/002246-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the mobilizable lactococcal plasmid pGdh442 encoding glutamate dehydrogenase activity

Abstract: A novel plasmid named pGdh442 had previously been isolated from a plant Lactococcus lactis strain. This plasmid encodes two interesting properties with applications in the dairy industry: a glutamate dehydrogenase activity that stimulates amino acid conversion to aroma compounds, and cadmium/zinc resistance that can be used as a selectable marker. Moreover, this plasmid can be transferred naturally to other strains, but appears to be incompatible with certain other lactococcal plasmids. During this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 58 publications
2
62
0
Order By: Relevance
“…NC_009435), featuring a single replication origin, the RepA replication initiation protein and the partitioning proteins ParA and ParB, thus confirming the prediction of Tanous et al (2007) that this is the reason for the plasmid incompatibility observed between these two plasmids. Located upstream of this region is a short CDS transcribed in the opposite direction, which has been annotated as repC on lactococcal plasmids pND324 (U44843.1) and pHP003 (AF247159.1) (Christensson et al, 2001), and is also present but not annotated on pIL105 (AF116286.2) (Anba et al, 1995).…”
Section: Replication Of Plp712supporting
confidence: 63%
See 3 more Smart Citations
“…NC_009435), featuring a single replication origin, the RepA replication initiation protein and the partitioning proteins ParA and ParB, thus confirming the prediction of Tanous et al (2007) that this is the reason for the plasmid incompatibility observed between these two plasmids. Located upstream of this region is a short CDS transcribed in the opposite direction, which has been annotated as repC on lactococcal plasmids pND324 (U44843.1) and pHP003 (AF247159.1) (Christensson et al, 2001), and is also present but not annotated on pIL105 (AF116286.2) (Anba et al, 1995).…”
Section: Replication Of Plp712supporting
confidence: 63%
“…S1), and putative D-Ldhs are only found in L. lactis plasmids pSK11P and pGdh442. Siezen et al (2005) (Tanous et al, 2007). Hence, there is no proof that the D-Ldh homologues found on pGdh442 and pSK11L are functional (Tanous et al, 2007;Siezen et al, 2005).…”
Section: Metabolic Functions Encoded By Plp712mentioning
confidence: 96%
See 2 more Smart Citations
“…Cheeses are rich in amino acids and peptides but the concentration of 2-OG is low. Supplementation of several types of cheeses with 2-OG led to a decrease in the levels of amino acids important for aroma development, which indicated that catabolism of these amino acids had been enhanced [137,138], and sensory analyses indicated that addition of 2-OG resulted in changes in creamy character, aroma intensity and fruity notes. These results clearly established that 2-OG availability is the limiting factor for the transamination reactions that convert aminoacids to aroma compounds and prompted scientist to look for sources of 2-OG.…”
Section: Aroma and Flavour Production By Lactic Acid Bacteria (Lab)mentioning
confidence: 99%